Experimental Study on a Passively Q-Switched Ho:YLF Laser with Polycrystalline Cr2+:ZnS as a Saturable Absorber*Supported by the National Natural Science Foundation of China under Grant Nos 61308009, 61405047, and 50990301, the Postdoctoral Science Foundation of China under Grant No 2013M540288, the Fundamental Research Funds for the Central Universities under Grant Nos HIT.NSRIF.2014044 and HIT.NSRIF.2015042, and the Science Fund for Outstanding Youths of Heilongjiang Province under Grant No JQ201310. (August 2015) - Cui, Zheng; Yao, Bao-Quan; Duan, Xiao-Ming; Li, Jiang; Bai, Shuang; Li, Xiao-Lei; Zhang, Ye; Yuan, Jin-He; Dai, Tong-Yu; Ju, You-Lun; Li, Chao-Yu; Pan, Yu-Bai
<x content-type="archive" xml:space="preserve">Abstract</x> Output performance of a continuous-wave Tm:YAP laser pumped passively Q-switched Ho:YLF laser is demonstrated with a polycrystalline Cr2+:ZnS as the saturable absorber. We compare the experimental results at the three different distances L of the polycrystalline Cr2+:ZnS saturable absorber to the output coupler. The pulse width almost remains constant for different L, when the incident pump power is changed in the range of 7.9–27.1 W. The shortest pulse duration of 33.3 ns for L = 105 mm and the highest average output power of 6.8 W for L = 5 mm are obtained at the incident pump power of 27.1 W. The output wavelength of the passively Q-switched laser shifts to 2045.2 nm from 2064.7 nm in the cw operation. The beam quality factor of M2 is 1.2.